Эффективность применения витаминно-минерального комплекса Витрум Кардио у детей с первичной артериальной гипертензией на стационарном этапе реабилитации - Алёшина, О.К. (Таврический медико-биологический вестник, 2013)
В умовах кардіоревматологічного стаціонару діти з первинною артеріальною гіпертензією отримали
базисну не медикаментозну терапію окремо і у поєднанні з вітамінно-мінеральним комплексом з іншими
добавками з метою корекції метаболічних порушень. Проведений порівняльний аналіз двох методик
лікування артеріальної гіпертензії. Доведена ефективність включення вітамінно-мінерального комплексу
в базисну не медикаментозну терапію. The children with primary arterial hypertension received basic non-drug therapy separately and in
combination with a vitamin and mineral complex with other additives for the purpose of correction of metabolic
disturbances in the conditions of a cardiorheumatologic hospital. The comparative analysis of two techniques of
treatment of arterial hypertension has been carried out. Efficiency of inclusion a vitamin and mineral complex
in basic non-drug therapy has been proved.